2023
DOI: 10.3390/polym15061484
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Fresh, Hardened, and Microstructural Properties of Fibre-Reinforced Geopolymer Concrete

Abstract: Alternative eco-friendly and sustainable construction methods are being developed to address growing infrastructure demands, which is a promising field of study. The development of substitute concrete binders is required to alleviate the environmental consequences of Portland cement. Geopolymers are very promising low-carbon, cement-free composite materials with superior mechanical and serviceability properties, compared to Ordinary Portland Cement (OPC) based construction materials. These quasi-brittle inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…Fiber is a commonly used reinforcing phase in composites, which can compensate for the loss of strength. It inhibits the generation of microcracks in concrete and improves the overall performance of concrete . There are two main forms of fiber reinforcement, namely, matrix fiber reinforcement and filled fiber-reinforced hollow materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber is a commonly used reinforcing phase in composites, which can compensate for the loss of strength. It inhibits the generation of microcracks in concrete and improves the overall performance of concrete . There are two main forms of fiber reinforcement, namely, matrix fiber reinforcement and filled fiber-reinforced hollow materials.…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits the generation of microcracks in concrete and improves the overall performance of concrete. 15 There are two main forms of fiber reinforcement, namely, matrix fiber reinforcement and filled fiber-reinforced hollow materials. Currently, the common filler fibers are mainly steel fibers, 16 carbon fibers, 17 glass fibers, 18 basalt fibers (BFs), 19 and polypropylene fibers (PPFs).…”
Section: Introductionmentioning
confidence: 99%
“…These applications have led to a growing focus on the use of FRC in place of traditional reinforcement. It is generally recognized that FRC materials can either be strain-hardening or strain-softening, depending on their response to tensile stresses, typically based on the number and type of fibers used [ 10 , 11 ]. After the first crack of the material has occurred, strain hardening can be distinguished by an increase in tensile stress, and it is also accompanied by multiple cracks [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of their experiments showed that using PVA rather than PP with limited layer thickness significantly enhances the maximum load capacity. Moreover, Asgari et al [ 11 ] describe experimental and numerical (section enlargement) methods for strengthening concrete beams with glass fiber-reinforced concrete. Experimental and numerical results demonstrated that using a glass fiber-reinforced concrete layer improves the load-carrying capability and ultimate deflection of concrete beams.…”
Section: Introductionmentioning
confidence: 99%